E-Learning experience of the "Virtual Campus of Sport" - Blazquez, D.; Calvo, J. (International Journal of Computer Science in Sport, 2003)
The educational uses of the information and communication technologies have been increasing considerably during the last years. We also realize that there is a need for improving the initial and continuous education of Sport Science professionals. The "Virtual Campus of Sport" tries to fit these considerations: it is an online learning program in the field of Sport Science.